Differential neuronal susceptibility and apoptosis in congenital Zika virus infection. Issue 1 (July 2017) - Ho, Cheng‐Ying; Ames, Heather M.; Tipton, Ashley; Vezina, Gilbert; Liu, Judy S.; Scafidi, Joseph; Torii, Masaaki; Rodriguez, Fausto J.; du Plessis, Adre; DeBiasi, Roberta L.
Abstract : To characterize the mechanism of Zika virus (ZIKV)‐associated microcephaly, we performed immunolabeling on brain tissue from a 20‐week fetus with intrauterine ZIKV infection. Although ZIKV demonstrated a wide range of neuronal and non‐neuronal tropism, the infection rate was highest in intermediate progenitor cells and immature neurons. Apoptosis was observed in both infected and uninfected bystander cortical neurons, suggesting a role for paracrine factors in induction of neuronal apoptosis. Our results highlight differential neuronal susceptibility and neuronal apoptosis as potential mechanisms in the development of ZIKV‐associated microcephaly, and may provide insights into the design and best timing of future therapy. Ann Neurol 2017;82:121–127